The Application of Target Costing in Determining the Selling Price at Suwar-Suwir Producers in Jember - Fitriyatul Amalia Febriana (Perkumpulan Praktisi Akuntansi Indonesia, 2020)
This research aims to know the determination of selling price of suwar-suwir at UD Purnama Jati and UD Mutiara Rasa using the target costing. This research is a descriptive qualitative research using interview, observation, and documentation methods, and using primary and secondary data. Based on the results of research conducted at UD Purnama Jati and UD Mutiara Rasa shows that the application of target costing through value engineering, the both of companies can still get a profit from selling price per unit of product that is 30% at UD Purnama Jati and 20% at UD Mutiara Rasa. So, if UD Purnama Jati and UD Mutiara Rasa want to increase the selling price of their suwar-suwir, the both of companies will get a greater profit. Therefore, it can be concluded that the application of target costing in this research shows success because the both of companies can determine the lowest selling price among the current market prices, but they still get the desired profit and can manage production costs well.